2009
DOI: 10.1097/gme.0b013e318182d352
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aerobic physical training on cardiac autonomic control of rats submitted to ovariectomy

Abstract: Ovariectomy did not change the tonic autonomic control of the heart and, in addition, reduced the participation of sympathetic component in cardiac modulation. Physical training, on the other hand, increased the participation of parasympathetic modulation on the HRV, including ovariectomized rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…Despite of some reports using normotensive rats have reported increases of arterial pressure post-ovariectomy (Mercier et al 2002;Thorin et al 2003;Irigoyen et al 2005;Souza et al 2007), our data match with almost all studies using normotensive rats, which did not show an increase in arterial pressure post-ovariectomy (Takezawa et al 1994a,b;Lam et al 2002;Brandin et al 2003;Abdel-Rahman 1998, 2004;Tezini et al 2008). In some of these papers, arterial pressure was also evaluated for long term by means of telemetry system, in which manipulation stress effects are absent (Takezawa et al 1994a,b;Brandin et al 2003;El-Mas and Abdel-Rahman 2004).…”
Section: Discussionsupporting
confidence: 83%
“…Despite of some reports using normotensive rats have reported increases of arterial pressure post-ovariectomy (Mercier et al 2002;Thorin et al 2003;Irigoyen et al 2005;Souza et al 2007), our data match with almost all studies using normotensive rats, which did not show an increase in arterial pressure post-ovariectomy (Takezawa et al 1994a,b;Lam et al 2002;Brandin et al 2003;Abdel-Rahman 1998, 2004;Tezini et al 2008). In some of these papers, arterial pressure was also evaluated for long term by means of telemetry system, in which manipulation stress effects are absent (Takezawa et al 1994a,b;Brandin et al 2003;El-Mas and Abdel-Rahman 2004).…”
Section: Discussionsupporting
confidence: 83%
“…When genders were compared, regardless of the level of physical conditioning, men presented an autonomic balance in favor of sympathetic modulation characterized by greater LF oscillations, whereas women presented an autonomic balance in favor of HF oscillations. These discrepant results were more evident in well-conditioned subjects (i.e., the moderate and high aerobic capacity groups), showing that gender can indeed influence cardiac autonomic modulation [31,46-48]. In accordance with these observations, the literature has shown that middle-aged women have the greatest variations in the spectral indices of HRV and lowest values of AP at rest conditions compared to men of the same age group.…”
Section: Discussionmentioning
confidence: 64%
“…In accordance with these observations, the literature has shown that middle-aged women have the greatest variations in the spectral indices of HRV and lowest values of AP at rest conditions compared to men of the same age group. This finding indicates that the female population would present an increased vagal cardiac modulation, which would be evidenced by higher HF values and lower LF values [30,46-48]. However, it was also shown that such a discrepancy in the spectral parameters of HRV decreases between men and women when their age is above 50 years old [46].…”
Section: Discussionmentioning
confidence: 99%
“…Exercise training may improve the cardiac autonomic balance by increasing vagal regulation while decreasing sympathetic regulation in rats (Souza et al 2007;Tezini et al 2009;Rossi et al 2009). It is an eVective means of reducing the levels of C-reactive protein, IL-1, IL-6 and interferongamma levels and increasing IL-10 levels in coronary artery disease patients, which collectively improve the coronary risk proWles (Goldhammer et al 2005).…”
Section: Hyperlipidemia Avects the Expression Of Cholinesterase-positmentioning
confidence: 97%
“…It is well accepted that exercise restores proWles of inXammatory cytokines and enhances the eVects of antiatherosclerotic agents (Adamopoulos et al 2002;Goldhammer et al 2005;Teixeira de Lemos et al 2009). Moreover, exercise has also been veriWed to increase HRV and BRS, lower blood pressure and reduce cardiovascular autonomic dysfunction in rats (Bertagnolli et al 2006;Souza et al 2007;Tezini et al 2009). However, there are no substantial studies to assess whether exercise may restore the function of cardiac vagus nerve in the hyperlipidemic heart, thereby improving cardiac function.…”
Section: Introductionmentioning
confidence: 98%